THE INFLUENCE OF FINTECH DIGITAL PAYMENT AND P2P LENDING ON INDONESIA’S ECONOMIC GROWTH - Yasir Maulana; Munir Nur Komarudin; Wely Hadi Gunawan; Ayus Ahmad Yusuf (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Studies suggest that financial innovations, or "Fintech," boost GDP. Due to social distance and business operations, fintech digital payment and lending have the edge over conventional financial institutions. Fintech lenders don't require face-to-face meetings. This study examines the influence of Fintech digital payment and peer-to-peer lending on Indonesia's economy. Use OJK statistics on peer-to-peer lending and fintech, Statista data on digital payments, and Bank of Indonesia data on economic growth as secondary sources. Digital Payment and P2P financing have a favorable but small influence on Indonesia's economic development, according to multiple regression. Digital Payments and P2P Lending Explain 88% of Economic Growth.